Lazer e processos educativos no contexto de trabalhadores/as rurais do MST - Silva, Robson Amaral da (2010)
Faced with the intensifying of competitive capitalist market and economic deregulation at the international level, enterprises turn their investments to regions and sectors with greater liquidity and in search of greater profits. In this direction, considering the logic of flexible accumulation, cultural goods and services are revealed as superfluous products, thus ensuring a rapid growing of capital. Therefore, the increase in supply and consumption of cultural goods linked to the field of leisure is no coincidence. Opposed to this trend are the followers of the Landless Workers' Movement (MST), seeking alternatives towards counter-hegemony able to sustain a new social design, a movement towards change directly associated with the field of leisure and education. Taking this into consideration, the presented qualitative research, inspired on existential phenomenology, sought the understanding of the ascribed meaning of leisure as perceived by members of the MST, as well as to describe the educational processes that underlie this social practice in areas of agrarian reform expropriated by the MST in the city and region of Ribeirão Preto. The literature review included issues such as social practices, educational processes, leisure, education, agrarian reform and MST, that together formed the conceptual bases for the study. Following my introduction in the group, and a period of coexistence, being recognized by men, women, children, young adults and the elderly members of this social movement, all events were recorded in field diaries, bringing the total number of fourteen diaries. Analysis of the diaries registered during the study went through the phases of ideographic analysis (identification of units of meaning) and nomothetic analysis (creation of the thematic categories and organization of the categories in the nomothetic matrix). The construction of the results was based directly on the data presented in the nomothetic matrix, which revealed the following categories: A) Leisure as a means to fight; B) Unequal appropriation of leisure by the female gender; C) Human development in day-to-day life in the MST : organization, environmental care, solidarity, community, sharing and resistance. The study shows that leisure activities can and should provide elements that support the (re)understanding of social responsibilities, selfrecognition and the (re)cognition of others, through the socializing character of these experiences, raising awareness to the feeling of solidarity and the value of opportunities that emerge in cultural experiences related to the context of rural workers of the MST. Manifestations that are expressed in the arts, sports, political activism, more broadly, in social life. The revolutionary character of praxis in the field of leisure is conditioned upon its accuracy in understanding the determination, or mediation, of economy, politics, culture and history in the sociability sewed under the auspices of globalized capital, with its strengths and contradictions, at the same time, having a glimpse of where the evidence coalesce the interests and strengths, the weaknesses and limits of the working class.